Efektivitas Permainan Ular Tangga Sebagai Media Penyuluhan Terhadap Pengetahuan Gizi Seimbang Siswa di SDN Landungsari 1 Kabupaten Malang - Adiba, Tahani Ratna; Supriyadi, Supriyadi; Katmawanti, Septa (Preventia: The Indonesian Journal of Public Health, 2020)
This study aims to determine how the influence of balanced nutrition counseling by using the game media snake ladder to the knowledge of balanced nutrition of students. This research use experimental research method with One Group Pretest Posttest type. The population in this study were all students in SDN Landungsari 1 Malang Regency. The sample in this research is the third grade students amounting to 35 children selected by purposive sampling. Knowledge measuring instruments are knowledge tests (pre-test and post-test). The analysis is paired sample T-Test with significance level of 0,05. The results showed that there was a difference of students' knowledge result between before and after counseling using balanced nutrition snake and ladder game media. It is based on the result of sig.p value of 0.00 and tcount of 15,245. Based on the above, it can be concluded that balanced nutrition counseling using game media of snake ladder can give influence to knowledge of balanced nutrition of student.